(untitled) (EAAE Annual Conference Proceedings, 2026)
One of the most relevant roles in architecture professional practice and, consequently, one of the most relevant issues to be taught in schools, is that of social leadership. In this will, almost duty, to guide society on the way to improving its quality of life and ensuring progress, architects have not always found the support of political and economic establishment and, occasionally, they have become developers of their own proposals. There are many buildings that have survived to the present day whose cost was totally or partially covered by the architects who designed them, in their eagerness to see them completed. And the current trend of refurbishing public spaces and buildings is no exception. In the Basque Country there is a deep-rooted tradition of meeting in small public or semi-public spaces called txokos or txakolines. In 1955 the Txakolin Zollo was built in Bilbao, one of the most popular of these places. However, two decades later, the commercial and bourgeois development of the two important streets connected by this alley led to an apparent divorce with the surrounding neighborhood. Given the lack of interest from the municipality, its neighbors decided to paint the walls and to treat the space in an experimental way, giving it a strong personality and turning it into an icon. But commercial activity decreased even more and with it came the progressive abandonment of this alley that reached the 2000s in very poor condition. In the early 2020s a young architect bought one of the premises and initiated a series of legal, but mainly architectural and social, actions that have made it possible to recover this space for the Bilbao citizenry and visitors. Aware of its value, its demolition was never an option. Commercial and public spaces have been refurbished and recovered, giving it back its own traditional activity but from a contemporary perspective. Newly inhabited by artisans and artists, the alley now has a presence on social media, hosts different kinds of events and enjoys a vibrant activity and a second chance as a commercial street thanks to the conviction and sponsorship of a young architect.